Implementasi geogebra pada numbered head together terhadap kemampuan pemecahan masalah matematis dan keaktifan belajar siswa SMP - Ramadannia, Cahyani; Nasrullah, Anton; Yendra, Novi; Sukmawati, Sri; Ratnasari, Silvia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research investigates the involvement and ability of junior high school students in solving mathematical problems by incorporating GeoGebra in the Numbered Head Together (NHT) approach. A dynamic mathematics application called GeoGebra and (NHT) is thought to offer improved problem solving and active learning. This research used a quasi-experimental with an equivalent control group design for State Middle School students in Cilegon City. Questionnaires and tests of mathematical problem solving abilities are the research instruments used. The analysis techniques used was prerequisite tests (normality test and homogeneity test), hypothesis testing (independent t test) and percentage of learning activity questionnaires. The results of data analysis show statistically significant differences between the control and experimental groups using GeoGebra on NHT learning and student engagement. The research recommendation from the research results is to encourage teachers to integrate dynamic software in the preparation and implementation of teaching using GeoGebra.